Habitat characteristics of the shelf distribution of the harbour porpoise (Phocoena phocoena) in the waters around the Faroe Islands during summer - Skov, Henrik; Durinck, Jan; Bloch, Dorete (NAMMCO Scientific Publications, 2003)
Observations from a large number of seabird line-transect surveys conducted in Faroese waters are used to derive some general conclusions regarding the distribution of harbour porpoises (Phocoena phocoena) in the region using estimates of encounter rates (no./km-1) in different meso-scale habitats around the Faroes during the breeding season (May-September). Based on a sub-set of the data collected during calm conditions (sea states below Beaufort 3) we analysed the distribution of harbour porpoises in relation to 5 potentially important physical parameters: water depth, distance to shore, slope of the ocean floor, distance to tidal front and Beaufort sea state. These parameters were determined from data collected during the surveys, the literature as well as from the new bathymetry established for the Faroese shelf. In order to link the differently scaled physical parameters with the encounter rates and sea states recorded during the surveys we used a suite of geo-statistical and raster-based GIS techniques based on a uniform grid resolution of 1 km in UTM zone 29 N projection. After removing parameters with insignificant effects a model of main effects was produced with sea state and distance to the tidal front having a significant negative effect on the rate of encountering harbour porpoises during both sets of cruises analysed (August 1997 and other surveys). During both sets of cruises the distance to the tidal front had a larger effect on the distribution of the animals than sea state. The strong relationship between harbour porpoise distribution and the average position of the tidal front around the Faroes strongly suggests that the species concentrates near the quasi-stationary circular shelf front separating mixed from stratified waters around the Faroes. However, the importance of shelf fronts for the distribution of harbour porpoises needs to be studied in detail in order to establish the proportion of the populations associated with these structures.